NH. DINI SEBAGAI PRIYAYI FEMINIS: TANGGAPAN EVALUATIF NH. DINI TERHADAP KEPRIYAYIAN JAWA DARI PERSPEKTIF WANITA - Lee Yeon (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Nh. Dini has been regarded as the pioneer in feminism, as the themes of her works convey her opinions about women’sissue in a society. Although she is likely to take side in her novels and often stands against social conventions and norms, she has shownappreciation toward the Javanese traditional cultural values, cultural values of the priyayi in her memoirs. This research has attempted toshow the way Nh. Dini draws a line between two contrary aspects, the cultural values of the priyayi and the women’s perspectives dan hasproven that basically Nh. Dini respects and accepts the values of priyayi, instead of exposing it as patriarchal system. What has become anissue for Nh. Dini is that the system has discriminated the implementation of the values of priyayi against women. By showing her faith in thevalues of priyayi and at the same time demanding equality between men and women, Nh. Dini appears with a new image as a feministpriyayi or a feminist who has faith in the values of priyayi